A level computer 3rd edition - Heathcote, P M (Letts Educational , London, 1998)
Third revised edition, updated for latest BTEC and BCS syllabuses and courses. The book is presented in ten self-contained sections, providing a complete two year course. It offers comprehensive coverage of A Level core topics, eliminating the need for handouts in classroom teaching. Can also be used to plan students' revision programmes.
Keywords: Computer science